2019
DOI: 10.1002/cctc.201900439
|View full text |Cite
|
Sign up to set email alerts
|

Considerations of Trends in Heterogeneous Photocatalysis. Correlations between Conduction and Valence Band Energies with Bandgap Energies of Various Photocatalysts

Abstract: A principal objective of our work was to illustrate the existence of unknown trends in the E CB = f(E bg ) and the E VB = f(E bg ) behavior for certain classes of compounds that also included a set of bismuthate photocatalysts; new trends may easily be hidden within more general trends. Indeed, when the data for the bismuthates are added to data related to novel visible-lightactive (VLA) photocatalysts, the trend remains the same with high significance levels for the E VB = f(E bg ) linear correlation. Using w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 59 publications
0
18
0
1
Order By: Relevance
“…Positions of the conduction band energies (E CB ) and of the valence band energies (E VB ) as a function of the bandgap energy (E bg ) for the set of calcium and strontium bismuthates. The data reported as filled red squares and circles correspond to the calcium bismuthates, whereas the data illustrated as filled green squares and circles correspond to the strontium bismuthates reported earlier by Shtarev et al [1] The red and green solid lines correspond to the linear correlations E CB (E bg ) and E VB (E bg ) for calcium and strontium bismuthate, respectively. The red and green dashed lines show the extrapolation of the resulting correlations to the intersection points at E bg = 0 eV.…”
Section: Methodsmentioning
confidence: 95%
See 4 more Smart Citations
“…Positions of the conduction band energies (E CB ) and of the valence band energies (E VB ) as a function of the bandgap energy (E bg ) for the set of calcium and strontium bismuthates. The data reported as filled red squares and circles correspond to the calcium bismuthates, whereas the data illustrated as filled green squares and circles correspond to the strontium bismuthates reported earlier by Shtarev et al [1] The red and green solid lines correspond to the linear correlations E CB (E bg ) and E VB (E bg ) for calcium and strontium bismuthate, respectively. The red and green dashed lines show the extrapolation of the resulting correlations to the intersection points at E bg = 0 eV.…”
Section: Methodsmentioning
confidence: 95%
“…In an earlier study, [1] we demonstrated a novel trend in the empirical dependence of the conduction and valence band positions on the bandgap energy of semiconductors for alkali earth metal bismuthate photocatalysts. [2] The dependences E CB = f(E bg ) and E VB = f(E bg ) for the bismuthates could be approximated by the linear functions E CB = A + B E bg and E VB = a + b E bg , respectively, thereby illustrating that bismuthates of alkaline earth metals formed a new trend in the field of semiconductor photocatalysts.…”
mentioning
confidence: 86%
See 3 more Smart Citations